Gambaran Pengelolaan Limbah Medis Padat di Rumah Sakit Islam Ibnu Sina Simpang Empat Tahun 2024 - Yusmia Rahdiani; Zulfa, Zulfa; Anne, Anne (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Hospital waste management in Indonesia is still not well managed, so there is still the potential for pollution to the environment around the hospital. Ibn Sina Simpang Empat Islamic Hospital produces an average of 50 kg/day of solid medical waste. Therefore, it is necessary to make efforts to improve hospital environmental health designed to protect the community and hospital staff as a result of environmental pollution originating from solid medical waste resulting from hospital activities. The purpose of this study was to determine the description of solid medical waste management at the Ibn Sina Simpang Empat Islamic Hospital in 2024. This research is descriptive research with a qualitative approach. Data collection through observation and interviews. The research informants were 8 people consisting of 1 head of environmental health 1 environmental health staff, 2 cleaning services, and 3 nurses. Based on the results of the study, it was found that solid medical waste management at the Ibn Sina Simpang Empat Islamic Hospital has not been managed properly. The process of sorting, packaging and transportation of hospital waste has not met the requirements. There is still solid medical waste mixed with non-medical waste. The lack of lanes used for waste transportation and the lack of waste shelters cause infectious and non-infectious waste to be mixed. The conclusion is that the implementation of medical waste management has not been carried out in accordance with Government Regulation Number 22 of 2021 concerning Guidelines for Environmental Protection and Management.